Impact of the National Health Insurance Program (JKN) on Access to Public Health Services: A Comprehensive Analysis - Syazarah Soraya; Talita Syamanta; Hilman Saidi Raja Bakkol Harahap; Coovadia Coovadia; Mario Greg (Insan Akademika Publications, 2023)
The National Health Insurance Program (Jaminan Kesehatan Nasional or JKN) has been a cornerstone of Indonesia's healthcare system, aiming to provide equitable access to public health services for its population. This research examines the impact of JKN on access to public health services in Indonesia, with a focus on enrollment duration, access barriers, satisfaction levels, and implications for policy and practice. A diverse sample of 800 JKN beneficiaries from various regions in Indonesia participated in this study. Demographic analysis revealed a broad representation of age, gender, education, and income levels among respondents. Data collection included structured surveys, interviews, and focus group discussions to capture comprehensive insights into the experiences of JKN beneficiaries. The research findings suggest that the duration of JKN enrollment significantly influences healthcare utilization. Beneficiaries enrolled for more than 2 years exhibited higher utilization rates, underscoring the importance of sustained enrollment. Access barriers, particularly long wait times and geographical distance to healthcare facilities, were identified as significant challenges. These barriers must be addressed to enhance healthcare accessibility. Satisfaction levels with healthcare services covered by JKN were generally high, but continuous quality improvement efforts are vital to sustain and elevate service quality. Policymakers can leverage these findings to promote long-term enrollment, address access barriers, and maintain equitable access to healthcare services. Healthcare providers can benefit from insights on improving appointment systems and ensuring quality care. The population at large can anticipate improved healthcare access as policy interventions seek to enhance the JKN program's effectiveness. In conclusion, this research contributes to the ongoing discourse on healthcare access in Indonesia, offering practical insights that can inform policy decisions and improve healthcare delivery. It underscores the importance of sustained JKN enrollment, the need to address access barriers, and the continuous pursuit of high-quality healthcare services for all Indonesians